Applications of three‐dimensional printing technology in urological practice. (23rd June 2015) - Youssef, Ramy F.; Spradling, Kyle; Yoon, Renai; Dolan, Benjamin; Chamberlin, Joshua; Okhunov, Zhamshid; Clayman, Ralph; Landman, Jaime
<x xml:space="preserve">Abstract</x> A rapid expansion in the medical applications of three‐dimensional (3D)‐printing technology has been seen in recent years. This technology is capable of manufacturing low‐cost and customisable surgical devices, 3D models for use in preoperative planning and surgical education, and fabricated biomaterials. While several studies have suggested 3D printers may be a useful and cost‐effective tool in urological practice, few studies are available that clearly demonstrate the clinical benefit of 3D‐printed materials. Nevertheless, 3D‐printing technology continues to advance rapidly and promises to play an increasingly larger role in the field of urology. Herein, we review the current urological applications of 3D printing and discuss the potential impact of 3D‐printing technology on the future of urological practice.